Relations Between Singapore and the People’s Republic of China in the Light of Donald Trump’s New Southeast Asia Policy - Chatys, Mateusz (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
The aim of the article is to analyze the relationship between Singapore and the People’s Republic of China in the light of the current policy of the President of the United States Donald Trump. The point of reference for the presented analysis is the foreign policy of the former President Barack Obama, based on the strategy known as “pivot to Asia” – the strategic turnabout of the United States to the Asia-Pacific region. One of its main objectives was the signing of a multilateral agreement on the establishment of a free trade zone, the Trans-Pacific Partnership (TPP), bringing together 12 countries. The main subject of the present analysis is to examine the impact of Donald Trump’s decision of January 2017 to withdraw from the TPP trade agreement on the relations between the remaining signatories of the agreement, as well as to examine Beijing’s actions, which may seek to increase its sphere of influence in Asia through the breakdown of TPP. The main part of the research is focused on the triangle politics concept in international politics, which will include China, Singapore and the United States. Besides the two largest economic powers, Singapore is included because of its membership in the TPP and ASEAN, and due to its strong economy and its population (predominantly) of Chinese origin it can be viewed as the “fifth column” or may otherwise play a role in the Greater China concept.